Perancangan dan Pembuatan Aplikasi Administrasi Kependudukan Kecamatan Golewa Barat dengan Pendekatan Berbasis Web - Selviana Nau; Emerensiana Ngaga; Alfry Aristo Jansen Sinlae (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2023)
In West Golewa District, the process of processing population and administrative data is still manual, using Microsoft Word and Excel in each village/urban village. Data storage in the form of physical documents poses a risk of data accumulation, loss, and corruption. Birth and death data are also poorly recorded, making it difficult to access valid population data. This research designed and created a web-based population administration application for West Golewa District. The web approach was chosen to improve people's accessibility when managing population data. The software development method used is waterfall with stages of analysis, design, coding, testing, and maintenance. This application has important features such as access to subdistrict information, downloadable E-KTP forms, requests for letters, online complaint submission, population data management, and statistical reports. It is expected that this web-based population administration application will increase the efficiency and accuracy of population data processing in West Golewa District. With easy access and automated processes, it is hoped that people can quickly access information, submit applications, and report complaints related to population administration. This application is expected to be an effective solution in the management of population administration in West Golewa District as well as an inspiration for similar developments in other regions.